Impacts of climate change on the agricultural and aquatic systems and natural resources within the CGIAR’s mandate - Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The document attempts to distil what is currently known about the likely impacts of climate change on the commodities and natural resources that comprise the mandate of CGIAR and its 15 Centres. It was designed as one background document for a review carried out by the High Level Panel of Experts on Food Security and Nutrition (HLPE) at the behest of the UN Committee on World Food Security (CFS) on what is known about the likely effects of climate change on food security and nutrition, with a focus on the most affected and vulnerable regions and populations. A total of 25 summaries covering 22 agricultural commodities, agroforestry, forests and water resources, present information on the importance of each commodity for food and nutrition security globally, the biological vulnerability of the commodity or natural resource to climate change, and what is known about the likely socio- economic vulnerability of populations dependent partially or wholly on the commodity or natural resource. With a few exceptions, the likely impacts of climate change on key staples and natural resources in developing countries in the coming decades are not understood in any great depth. There are many uncertainties as to how changes in temperature, rainfall and atmospheric carbon dioxide concentrations will interact in relation to agricultural productivity; the resultant changes in the incidence, intensity and spatial distribution of important weeds, pests and diseases are largely unknown; and the impacts of climate change and increases in climate variability on agricultural systems and natural-resource-dependent households, as well as on food security and the future vulnerability of already hungry people in the tropics and subtropics, are still largely a closed book. CGIAR along with many other partners is involved in a considerable amount of research activity to throw light on these issues.